2013
DOI: 10.4269/ajtmh.12-0401
|View full text |Cite
|
Sign up to set email alerts
|

A Subregional Analysis of Epidemiologic and Genetic Characteristics of Influenza A(H1N1)pdm09 in Africa: Senegal, Cape Verde, Mauritania, and Guinea, 2009–2010

Abstract: Abstract. During the pandemic 2009 episode, we conducted laboratory-based surveillance in four countries from West Africa: Senegal, Mauritania, Cape Verde, and Guinea. Specimens were obtained from 3,155 patients: 2,264 patients from Senegal, 498 patients from Cape Verde, 227 patients from Mauritania, and 166 patients from Guinea; 911 (28.9%) patients were positive for influenza, 826 (90.7%) patients were positive for influenza A, and 85 (9.3%) patients were positive for influenza B. Among the influenza A posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…Seasonality in influenza transmission is consistent with findings from other tropical countries1, 14, 15, 16 including Tanzania17 and Brazil 18. In Senegal, influenza peaks also generally correspond to months with higher precipitation and humidity 19, 20…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Seasonality in influenza transmission is consistent with findings from other tropical countries1, 14, 15, 16 including Tanzania17 and Brazil 18. In Senegal, influenza peaks also generally correspond to months with higher precipitation and humidity 19, 20…”
Section: Discussionsupporting
confidence: 86%
“…18 In Senegal, influenza peaks also generally correspond to months with higher precipitation and humidity. 19,20 As in Senegal and Brazil, seasonal influenza peaks generally correspond with the two rainy seasons in Ghana: May-June and August-September. Interestingly, the timing of precipitation (and corresponding increased humidity) and influenza case peaks correspond to regional climatic differences; southern Ghana experiences earlier case and precipitation peaks than northern Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Six samples were also found to be positive for IAV H1N1 subtype while only three samples were positive for IBV. Interestingly, based on the HA gene sequences that were retrieved in this study, five of the IAV isolates clustered together with the sequences reported from Uganda and southern Russia [95].…”
Section: Mauritaniasupporting
confidence: 73%
“…The HA1 gene sequences were retrieved from one of the isolates, which phylogenetically clustered together with the sequences reported from the USA and China. [95].…”
Section: Cape Verdementioning
confidence: 99%
See 1 more Smart Citation